Talking About End-of-Life Care: How Should Physicians Act (Community Based Medical Journal, 2021)
Physicians should be adept in communication and familiar with the various end-of-life issues and their implications. However, physicians in Bangladesh usually receive very little training or guidance on how to communicate with the dying patients and their families. Since death is a common phenomenon, for physicians in their day-to-day practice, it sometimes becomes difficult to engage in end-of-life discussions in a death-averse society. This review paper aims to discuss a pragmatic step-by-step approach to discussing end-of-life care in a Bangladeshi context maintaining local social and cultural views. Specifically outlined in each of these four steps, a physician should seek a common understanding with the patient and family. Moreover, if any disagreement arises, overt conflict can often be avoided by reviewing what was discussed earlier with the patient or family. We all know that providing a supportive care for a dying patient is challenging. However, when it is done well, it becomes a meaningful and gratifying experience for the physician. As we know, helping someone die in comfort and with dignity signifies a good death and one of the best gifts of life that theoretically leads him/her to rest in peace.CBMJ 2020 January: Vol. 09 No. 01 P: 38-42